Pashupati seal - from the Indus Valley Civilization - Wiki commons (2022)
By unknown Indus Valley Civilization sealmaker from Mohenjodaro archaeological site - http://www.columbia.edu/itc/mealac/pritchett/00routesdata/bce_500back/indusvalley/protoshiva/protoshiva.jpg, Public Domain, https://commons.wikimedia.org/w/index.php?curid=9325528